T-RFLP analysis of bacterial communities in the midguts of Apis mellifera and Apis cerana honey bees in Thailand - Disayathanoowat,T. (Wiley-Blackwell, 2015)
This study investigated bacterial community structures in the midguts of Apis mellifera and Apis cerana in Thailand to understand how bacterial communities develop in Apis species. The bacterial species present in replicate colonies from different locations and life stages were analysed. PCR amplification of bacterial 16S rRNA gene fragments and terminal restriction fragment length polymorphism analyses revealed a total of 16 distinct terminal restriction fragments (T-RFs), 12 of which were shared between A. mellifera and A. cerana populations. The T-RFs were affiliated to Beta- and Gammaproteobacteria, Firmicutes and Actinomycetes. The Gammaproteobacteria were found to be common in all stages of honey bee, but in addition, the Firmicutes group was found to be present in the worker bees. Bacterial community structure showed no difference amongst the replicate colonies, but was affected to some degree by geographical location, life stage and species of honey bees. © 2011 Federation of European Microbiological Societies. Published by Blackwell Publishing Ltd.